The Strategy of Belarus in the Context of Global Actors Policy - Sergey Anatolyevich Kizima (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
Republic of Belarus is an average by the size the sovereign state forming the strategy taking into account policy of the global players who are carried out in the East European region. The attitude towards Belarus of global actors (the USA, the EU, China and Russia) and the repertoire of steps taken by Minsk depend on a set of factors which analysis is carried out in the first part of the article. It is noted that Belarus as the player in the region of Eastern Europe has not completely created the policy yet. New opportunities for formation of the strategy of the Belarusian policy adequate to national interests have appeared because of revaluation of a role of Belarus as important donor of safety in the region against the background of efforts of Minsk on settlement of the Ukrainian crisis.